The The Description of the Nutritional Care of Patients Cirrhosis Hepatic with Hematemesis Melena on Regional General Hospital Dr. Saiful Anwar Malang - Wira Triangga Yusminingrum (Jurnal Informasi Kesehatan Indonesia (JIKI), 2019)
ABSTRACT Hepatic Cirrhosis is a chronic disease in the liver with liver inflammation and fibrosis which results in distortion of the liver structure and loss of most liver functions. The cause of the emergence of hepatic cirrhosis in western countries most often is alcoholic involvement while in Indonesia the most is caused by hepatitis B or C virus. To find out the description of nutrition care including Assessment, Diagnosis, Intervention, Monitoring and Evaluation in Hepatic Cirrhosis patients with Hematemesis Melena at the Regional General Hospital Dr. Saiful Anwar Malang. The research design used is analytic observational study with case study design that is by observing nutritional care in hepatic cirrhosis patients with hematemesis melena at the Inpatient Installation 1 of Internal Medicine (IPD) Regional General Hospital Dr. Saiful Anwar on 2 to 30 April 2018. The study subjects were 6 patients. Data collection by interviewing, observing, measuring and calculating directly on patients, families and room nutritionists. The data obtained are presented in tables and graphs and analyzed descriptively. The results showed that to assess nutritional status using LILA, there were 4 patients with poor nutritional status to worse. Biochemistry in the initial data obtained hemoglobin and hematocrit in 5 low patients, erythrocytes 6 patients low, 6 patients with anemia, high 5 leukocytes patients, SGOT 5 patients high, SGPT 5 patients low and 5 patients with low albumin. Physical examination of hepatic cirrhosis patients showed that 6 patients (100%) had weakness, colored urine, decreased appetite and abdominal pain, 5 patients (83.33%) experienced nausea, yellow eyes, black defecation, ascites and shortness of breath, and 4 patients (66.67%) had edema, whereas on clinical examination of hepatic cirrhosis patients showed 3 patients (50%) with low blood pressure, 4 patients (66.67%) with normal pulse, 4 patients (83.33% ) with low temperature and 5 patients with GCS light at the time of the initial examination. In the past history, the most common causes were hepatitis B virus, nutritional history before 4 patients often consumed tea and coffee more than 3 times a day and in the nutritional history now 4 patients with energy, protein and fat intake were in the poor category, while 6 patients with carbohydrate intake in the less category. Nutritional diagnoses used were NI-2.1, NI-5.2, NI-5.4 and NB-1.1 domains. Nutritional interventions provided are giving or modifying, the type or amount of food and nutrients at a certain time (ND-1.2) and the provision of education related to eating arrangements according to the patient's condition (E-1.1). In the monitoring and evaluation of 4 patients with poor nutritional status to poor, biochemical fluctuations in 6 patients, 4 patients with increased blood pressure, 3 patients experienced a decrease in GCS or awareness and fluctuating food intake in 6 patients. From the results of the study found 6 patients at risk of malnutrition using SGA and MUST, while the assessment of nutritional status using anthropometric measurements of upper arm circumference (LILA) 4 patients experienced poor nutritional status to worse. The average level of energy, protein, fat and carbohydrate consumption is still in the poor category, this is because food is given gradually. Anthropometry development has not increased, biochemical examination has not improved, laboratory tests have changed every day and physical conditions in 5 patients have decreased. Families are needed to monitor behavior changes in patients. Keywords: Hepatic Cirrhosis, Nutritional Care, Hospital